Possibilidade habermasiana de ação emancipatória entre pesquisador-pesquisa(n)do em educação popular - Vasconcelos, Giuliana Cavalcanti (2010)
in 1999 United Nations Educational, Scientific and Cultural Organization (UNESCO) documented that what distinguishes the poor from the rich is the reality in which we put popular subjects on the margin of creation and scientific benefits. According to Jürgen Habermas, on the principle of subjectivity, research practices has strengthened this duality and intensified scientific marginalization. Researchers, enclosed in a colonialist conscience, have been producing science and modernity. They expelled images of world and renounced interpretation about history. Scientific interaction witch popular classes were discarded. Social integration practices by means of interaction through language medium were lost. All this prevented a fusion of subjectivities in the horizon of a shared emancipation. The subjects of research were limited to the condition of being instruments of data collect, observation of occurrences, scientific impartialities or denouncing partialities. Nowadays, researchers do still use methodologies that treat popular subjects as objects of scientific knowledge. This lead us to question about the possibility that shared emancipatory actions could be put into effect in popular educational research. In order to reflect on the problem, a research on the published production about popular education by Associação Nacional de Pós-Graduação e Pesquisa em Educação (ANPED) was carried out and the ultimate annual meetings in 2008 and 2009 were also highlighted. The delimited interpretative categories were instrumental actions and communicative actions from habermasian perspective. The interpretative methodological foundation used was that of hermeneutics also from a habermasian perspective. In the course of study we came to understand that an instrumental acting leave researchers deprived of creative and illocutionary strength. This kind of acting does not assure access to non-thematic knowledge and knowledge of a living world that express themselves by means of acts of speech. With no interactive links with subject of research, there is not a way to reach the field of vision as far as an experienced world is concerned. The adoption of the principle of inter-subjectivity offers possibilities for rethinking an emancipatory action under a proposition of a communicative action in researches. Reciprocity brings about forms of legitimizing collaborative authorship of subjects of research in creation and use of scientific benefits. Instrumental will can be substituted for a social integration as a result of a shared emancipation. We came to conclude that the communicative acting is an habermasian possibility of fomenting emancipatory actions between researcher and subject of research in popular education.